Comparative Study of Ultrasound and Magnetic Resonance Imaging of Adnexal Masses - Narikelapu Nitya; Rama Krishna Rao Baru (Asian Journal of Medical Radiological Research, 2020)
Background: Current study aimed to assess the role of ultrasound and MRI in the evaluation of adnexal mass lesions and comparison with clinical outcomes. Subjects & Methods: A total of 30 suspected adnexal mass detected on ultrasonography was performed MRI, and accuracy of both USG and MRI were compared with histopathology. Results: Abdominal pain was predominantly confined to the lower abdomen in13 of 30 cases (43.3%). On USG total number of benign lesions was 19, and the total number of malignancies was 11. However, on MRI, 21  cases were mild, and 9 cases were malignant. six cases were diagnosed as malignant in ultrasound. In these six cases, two cases were serous cystadenocarcinoma, two were mucinous cystadenocarcinoma, one was serious papillary cystadenocarcinoma of the fallopian tube, and one was a malignant tubo-ovarian mass. MRI accurately diagnosed 4 indeterminate cases that correlated with the histopathology report. 9 malignant lesions were diagnosed as malignant by MRI were 3 cases of serous cystadenocarcinoma, 2 cases of mucinous cystadenocarcinoma, 1 case of malignant tubo-ovarian mass, 1 case of endometrioid carcinoma, 1 case of serous papillary cystadenocarcinoma of the fallopian tube and 2 cases of malignant sex cord-stromal neoplasms. Both the cases of serous cystadenomas were correctly diagnosed as benign lesions on both ultrasound and MRI. There were 2 cases of mucinous cystadenocarcinoma, which were accurately diagnosed as malignant on both USG and MRI due to the presence of solid components, mural thickening. The sensitivity, specificity, and accuracy of USG were 36.6%, 94% and 55% respectively. The sensitivity, specificity, and accuracy of MRI were 81.80%, 94.7%, and 65.7%, respectively. Conclusion: The best agreement was observed between MR findings and diagnosis in origin, tissue content, and tissue characteristics. Sonography had a weak correlation in context to the definitive diagnosis for the origin and tissue content of a mass.